The yield curve slope and monetary policy innovations - Edward N. Gamber; Frederick L. Joutz (Institute for Advanced Studies (IHS), 2005)
We separate changes of the federal funds rate into two components; one reflects the Fed's superior forecasts about the state of the economy and the other component reflects the Fed's reaction to the public's forecast about the state of the economy. Romer and Romer (2000) found that the Fed reveals information about inflation when it tightens monetary policy. Their research has implications for measuring monetary policy as well. When the Fed raises short-term interest rates it leads to some combination of increased inflationary expectations and an increased real rate. In this paper we estimate a structural VAR that allows us to separate out (identify) components of federal funds changes that are due to inflationary expectations (thus neutral) and that part which is contractionary. Our measure of monetary policy is the part of federal funds changes that exclude the Fed's revelation of its asymmetric information about future inflation.
Keywords: E31; E43; E52; 330; monetary policy; yield curve; inflation; price puzzle; Geldpolitik; Inflation; Rendite; Zinsstruktur; VAR-Modell; Theorie